2009
DOI: 10.1038/eye.2009.131
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety in a non-population-based, pre-publicised glaucoma screening exercise

Abstract: Objective To investigate whether anxiety plays a role in self-recruitment for non-population-based glaucoma screening. Methods In a non-population-based pre-publicised trial, self-recruited Caucasian participants were screened for glaucoma, and also completed the Trait Anxiety Inventory and Shortened Health Anxiety Inventory questionnaires. In pre-publicity for the trial, information on risk factors for glaucoma was given. Participants classified as possible glaucoma cases later underwent a detailed glaucoma i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…Regarding anxiety, and in contrast to Hollo et al 31 and Cumurcu et al, 13 this study shows higher state-and trait-anxiety scores among patients with progressed glaucoma, as compared with the control group. These differences were significant for the Trait-Anxiety score (p=0.028), suggesting a persistent effect of the illness on anxiety features.…”
Section: Depression and Anxietycontrasting
confidence: 95%
“…Regarding anxiety, and in contrast to Hollo et al 31 and Cumurcu et al, 13 this study shows higher state-and trait-anxiety scores among patients with progressed glaucoma, as compared with the control group. These differences were significant for the Trait-Anxiety score (p=0.028), suggesting a persistent effect of the illness on anxiety features.…”
Section: Depression and Anxietycontrasting
confidence: 95%
“…Narrowing of the target population is highly desired. Prepublicizing the risk factors for glaucoma does not seem to increase the number of patients successfully screened, for in self-recruited screening, overall health anxiety may surpass the actual rate of risk factors present [36]. Several studies suggest that there is a possible relationship between diabetes and POAG, the condition occurring almost twice as often in diabetics than in nondiabetics [37,38].…”
Section: Possible Applications In Ophthalmologymentioning
confidence: 99%
“…Early detection and treatment are essential to prevent vision loss due to glaucoma, but often the early symptoms are ignored, and most people do not go for their regular eye examinations. It has been found that 50% of glaucoma cases go undetected in the early stages (Holló et al 2010, Lagrèze 2010). Thus, an easy and inexpensive test that can be performed routinely and used for population screening could help detect the disease in the early stages and prevent millions of people from suffering from vision loss.…”
Section: Introductionmentioning
confidence: 99%